Rapid LC‐MRM‐MS assay for simultaneous quantification of choline, betaine, trimethylamine, trimethylamine N‐oxide, and creatinine in human plasma and urine. Issue 18 (13th August 2015) - Zhao, Xueqing; Zeisel, Steven H; Zhang, Shucha; Barbas, Coral
<x xml:space="preserve">Abstract</x> There is a growing interest in analyzing choline, betaine, and their gut microbial metabolites including trimethylamine (TMA) and trimethylamine N‐oxide (TMAO) in body fluids due to the high relevance of these compounds for human health and diseases. A stable isotope dilution (SID)‐LC‐MRM‐MS assay was developed for the simultaneous determination of choline, betaine, TMA, TMAO, and creatinine in human plasma and urine. The assay was validated using quality control (QC) plasma samples, spiked at low, medium, and high levels. Freeze‐thaw stability was also evaluated. The utility of this assay for urine was demonstrated using a nutritional clinical study on the effect of various egg doses on TMAO production in humans. This assay has a wide dynamic range (R2 > 0.994) for all the analytes (choline: 0.122–250 μM; betaine: 0.488–1000 μM; TMA: 0.244–250 μM; TMAO: 0.061–62.5 μM; and creatinine: 0.977–2000 μM). High intra‐ and inter‐day precision (CV < 6%) and high accuracy (< 15% error) were observed from the QC plasma samples. The assay is reliable for samples undergoing multiple freeze‐thaw cycles (tested up to eight cycles). The assay also works for urine samples as demonstrated by a clinical study in which we observed a significant, positive linear response to various egg doses for urinary concentrations of all the analytes except creatinine. A rapid SID‐LC‐MRM‐MS assay for simultaneous quantification of choline, betaine, TMA, TMAO, and creatinine has been developed and validated, and is expected to find wide application in nutrition and cardiovascular studies as well as diagnosis and management of trimethylaminuria.